2021
DOI: 10.1186/s12992-021-00698-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring fear of COVID-19 and its correlates among older adults in Bangladesh

Abstract: Objective This study was aimed to assess the perceived fear of COVID-19 and its associated factors among older adults in Bangladesh. Methods This cross-sectional study was conducted in October 2020 among 1032 older Bangladeshi adults aged ≥60 years. A semi-structured questionnaire was used to collect information on participants’ characteristics and COVID-19 related information. Perceived fear of COVID-19 was measured using the seven-item Fear of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
93
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 41 publications
(39 reference statements)
22
93
2
5
Order By: Relevance
“…While there is scarce evidence on COVID 19 fear among Nepalese older adults, our findings align with the recently published evidence that reported fear, psychosocial effects, and uncertainty due to COVID-19 in Nepal and other settings [25][26][27][28]. A recent study from Bangladesh reported a higher COVID-19 fear among Bangladeshi older adults [26]. Variations in older adult's responses on items of fear scale might differ across settings because of different levels of emotional responses to the phenomenology of the pandemic, such as desist warnings, unending uncertainty, and concern over people's death amid COVID [29,30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While there is scarce evidence on COVID 19 fear among Nepalese older adults, our findings align with the recently published evidence that reported fear, psychosocial effects, and uncertainty due to COVID-19 in Nepal and other settings [25][26][27][28]. A recent study from Bangladesh reported a higher COVID-19 fear among Bangladeshi older adults [26]. Variations in older adult's responses on items of fear scale might differ across settings because of different levels of emotional responses to the phenomenology of the pandemic, such as desist warnings, unending uncertainty, and concern over people's death amid COVID [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Rapid spread of COVID-19, extensive news coverage portraying older adults' vulnerability to the infection coupled with COVID-19 misinformation and challenges to access health care may explain why older adults were more fearful. However, in contrast to our findings, a study conducted in Bangladesh did not find an association between older adults' age and fear of COVID-19 [26]. This discrepancy could be because of differences in study settings and small number oldest age category in the Bangladeshi study.…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…Generally, females are highly prone to mental health suffering, a finding that is also consistent with the pandemic-related Bangladeshi studies [ 7 , 8 ]. In addition, the female gender is being reported to have higher knowledge and fear of COVID-19 [ 31 33 ], which can be the risk predictors of such a situation because other studies reported COVID-19 fear increasing sleep problems [ 18 ]. Also, participants reporting higher COVID-19 risk in this study are prone to be insomniacs.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 However, there has been a lack of studies assessing fear of COVID-19 compared with other aspects of mental suffering, including depression, anxiety and stress, in Bangladesh. 11 To the best of the author's knowledge, three studies have assessed risk factors for fear of COVID-19 across different cohorts (i.e., the general population, 12 the general population and healthcare professionals, 4 and older adults 13 ), whereas another study explored its mediating role in career anxiety among students. 2 However, none of these studies considered such a large sample as that used in the present study, provided any predictive models explaining the fear of COVID-19, or considered its nationwide spatial distribution.…”
Section: Introductionmentioning
confidence: 99%